A Survey on The Current Applications of Pattern Recognition in Various Fields - Harpreet Kaur (AG Volumes, 2022)
Automated pattern recognition is the process of identifying patterns and trends in a dataset. Over the last several decades, techniques for identifying patterns in data have advanced significantly. Many fields of science and engineering rely on automated and machine-based methods for pattern identification, description, categorization, and grouping. These include fields such as biological science and psychology to medical science and marketing to computer vision including artificial intelligence. This article will cover what pattern recognition is, the forms of pattern recognition, and analyze forms of pattern recognition in artificial intelligence.